Gender analysis of the effects of the operation and organization of AICCRA-ANCAR cooperatives on members - Mbow, Khalifa; Diallo, Abdoulaye Moussa; Sarr, Etienne Alouise; Worou, Nadine; Huyer, Sophia; Folorunso, Akinseye; |Wane, Abdrahmane; Thiaw, Moussa; Diedhiou, Lamine (International Livestock Research Institute, 2024)
The collaboration between AICCRA and ANCAR resulted in the establishment of agricultural cooperatives that use climate-smart farming techniques and a climate information system (CIS) to boost farmers’ incomes. This study evaluates this initiative and its socio-economic impact in three cooperatives: the Niayes, the agrosylvopastoral zone, and the peanut basin. Using qualitative focus groups (n=56), results highlight cooperatives' role in improving members' lives, particularly women and youth. Climate information, improved seeds, and innovative practices increase resilient agriculture knowledge and productivity. Success prompts neighbouring farmers to purchase seeds from beneficiary cooperatives. Despite limited land access, women and young cooperative members experience increased incomes and improved economic and social situations through AICCRA-Senegal's provision of climate information and quality seeds. The initiative's success demonstrates the potential of climate-smart agriculture in enhancing rural livelihoods and promoting sustainable development in Senegal.